CESifo World Economic Survey May 2016 - Johanna Garnitz; Gernot Nerb; Klaus Wohlrabe; Dorine Boumans; Katrin Oesingmann; Till Nikolka (CESifo World Economic Survey, 2016)
World Economic Climate: World Economic Climate brightens slightly - Economic Expectations: Economic expectations upwardly revised - Inflation: Inflation expectations continue to pick up - Currencies: US dollar expected to rise further - Interest Rates: Interest rate trends set to diverge - Special Topic: Immigration policies
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies